EQUILITAS RASIO LIKUIDITAS SEBAGAI TOLAK UKUR KINERJA KEUANGAN BANK BRI SYARIAH PERIODE 2015-2019 - Andreanto Indra Pratama; Tsaqif Fadhlilhaq; Renny Oktafia (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This progress intends to evaluate the financial work of PT bank BRI syariah. during 2015 to 2019 with a focus on liquidity aspects. The company this time is in a more accurate position in terms of calculations in secondary data. The processing and programming used is by using sampling methods and planned decisions. As for the data analysis activities that are used, namely liquidity analysis.From this decision, we can see that BRI sharia banks are on. From 2015 to 2019 when viewed from its liquidity ratio, it has a good proportion in the financial sector. This is reflected in the Quick Ratio that has met Bank Indonesia (BI) standards which are in the range of 10-20%. Banking Ratio is also considered quite good, in the range of 70-81%, where BI standard is 85 to 100%. The Loan to Deposit Ratio, which ranges from 63 to 73%, is also within the accepted limit of ≤98% in accordance with BI regulations. Meanwhile, the Loan to Asset Ratio which ranges from 56-67% indicates that the bank maintains a position lower than Bank Indonesia's regulatory limit set at more than 10%. This shows that PT Bank BRIsyariah Tbk has the ability to manage debt payments at a predetermined time, as well as has the capacity to overcome potential defaults in providing financing and providing guarantees for loans provided to customers